Canadian Universities, Academic Freedom, Labour, and the Left - Horn, Michiel (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2000)
Abstract During most of their history, Canadian universities, institutions staffed by and serving largely middle class people, have not been hospitable to organized labour or the political left. Professors who expressed support for such causes generally found that doing so often strained the limits of academic freedom as it was understood by governing boards, administrators, a good many academics, and many people outside the institutions. If the situation has improved during the last three decades, one reason is that faculty unions have become commonplace. More important, however, may be that the outside world has come to pay less attention to what professors say, on almost any subject, than used to be the case.